E-Learning Web Elements for Brickwork Course in the Construction Technology for Vocational Training - Mahmud, Murni Farahin; Yee, Mei Heong; Mohamad, Mimi Mohaffyza; Azid, Nurulwahida; Nur Rahma Putra, Andika Bagus (Journal of Technical Education and Training, 2024)
E-learning web is a learning material delivered in electronic media through HTML (Hyper Text Markup Language), programming for the Construction Technology Program. This study was conducted to design and develop reference material as an e-learning web for the brickwork course based on modifying the ADDIE model. The objective of this study is to identify the aspects of web element requirements, the appropriateness of design, format, and content in the e-learning web of the brickwork course and the usability of the e-learning web. This study is a development and survey involving three types of respondents: three creative multimedia experts from Universiti Tun Hussein Onn Malaysia, lecturers, and students in construction technology programs from vocational colleges. The questionnaires and feedback forms were used using dichotomous and Likert scales. The results of the study indicated that all lecturers and students agree with the appropriateness of the design, format, content, and usability of the e-learning web. Overall, the development of the e-learning web of the brickwork course for the construction technology program is expected to help improve student understanding and be beneficial as an input for web developers, especially for developing educational materials for Web 4.0.